2021
DOI: 10.3390/su13168799
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Motivation Sources as Pillars of Sustainable Internal Marketing Communication in Turbulent Post-Pandemic Times

Abstract: The main aim of the article is to identify the changes in employees’ sources of intrinsic motivation caused by the impact of the COVID-19 pandemic, and to discuss prospective modifications to formulated patterns of internal marketing communication. The novelty of the research lies in two main aspects: (1) the necessity to revise the traditional concept of motivation caused by the pandemic and (2) own methodological approach. While the first aspect reflects the lack of appropriate scientific attention paid to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…It is one of the new innovative methodologies in personnel management. Majerova et al (2021) identified the phenomenon of the extrinsic notion of internal factors, which indicates the need for effective communication as a stimulus for the optimal functioning of the model when it comes to internal motivation of individual employees. It can be argued that existing principles and patterns of internal marketing communication should be critically reviewed, and incentive systems should be revised to contribute to the company's optimal market performance and sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is one of the new innovative methodologies in personnel management. Majerova et al (2021) identified the phenomenon of the extrinsic notion of internal factors, which indicates the need for effective communication as a stimulus for the optimal functioning of the model when it comes to internal motivation of individual employees. It can be argued that existing principles and patterns of internal marketing communication should be critically reviewed, and incentive systems should be revised to contribute to the company's optimal market performance and sustainable development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In return, when working conditions are bearable and engaging, employees effectively commit to their work with POS, which states that good working conditions during COVID-19 pandemic and the adequacy of employee tools help employees to effectively carry out their work (Giorgi et al, 2020). In line with internal marketing, employee work is easy when adequately executed as part of work engagement especially during COVID-19 pandemic (Majerova et al, 2021;Nemteanu and Dabija, 2021). Thus, we propose the following hypotheses.…”
Section: Congruent Internal Marketing and Its Impact On Work Engagementmentioning
confidence: 97%
“…However, it is not a general rule. When creating a motivational system, the individual characteristics of the employee profile must therefore be taken into account ( Majerova et al, 2021 ). van Tuin et al (2020) demonstrated that motivation positively affects work engagement.…”
Section: Literature Reviewmentioning
confidence: 99%